Lower symptoms of disordered eating and training behaviour and depression in national team gymnasts compared to healthy controls - Melin, A.; Forsberg, N.; Edlund, K. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Compulsive Exercise (CE) is characterised by excessive and increasing training loads, abstinence without training and an inability to reduce exercise amounts. In females CE is often associated with disordered eating behaviour (DE). Potential harmful consequences are injuries, depression and impaired social relations. Studies comparing the prevalence of CE, DE and depression among aesthetic athletes and healthy controls are scarce. We therefore aimed to investigate CE and DE among individual and team national team gymnasts and healthy controls.